ANALYSIS OF SELECTED TRANSPORTATION NETWORK STRUCTURES BASED ON GRAPH MEASURES - Renata ŻOCHOWSKA; Piotr SOCZÓWKA (Scientific Journal of Silesian University of Technology. Series Transport)
The structure of transportation networks has been the subject of analysis for many years, due to the important role that it plays in assessing the efficiency of transportation systems. One of the most common approaches to representing this structure is to use graph theory, in which elements of transportation infrastructure are depicted by a set of vertices and edges. An approach based on graph theory allows us to assess the structure of a transportation network in terms of connectivity, accessibility, density or complexity. In the paper, different transportation network structures are assessed and compared, based on graph measures.